The relationship of Palaeozoic metamorphism and S-type magmatism on the paleo-Pacific Gondwana margin - Scott, J.; Muhling, J.; Fletcher, Ian; Billia, M.; Palin, J.; Elliot, T.; Gunter, C. (Elsevier BV, 2011)
A massive pulse of granitic magma was rapidly emplaced into the once contiguous West Antarctic and New Zealand segments of the palaeo-Pacific margin of the Gondwana supercontinent at ~ 371 Ma. In New Zealand, these Late Devonian S-type granitoids cover an areal extent of > 3400 km2, but the tectonic setting for crustal partial melting has remained unclear because most of the exposure represents either emplacement-level, or rocks that have been reworked during Cretaceous orogenesis. New petrologic data indicate that aluminous paragneisses and orthogneisses in the Bonar Range represent a rare portion of Devonian middle crust that preserves evidence for the initiation of crustal melting. The investigated rocks outline the tail of a clockwise P–T path that involved partial melting at peak conditions (~ 670 °C, 5.1 kb), deformation during the immediately following near-isothermal decompression, and then partial re-equilibration under static conditions. Syn- to post-kinematic growth of zoned monazite establishes the timing of recrystallisation to a ~ 16 Ma period that began at 373.4 ± 4.1 Ma. This age overlaps with the initiation of regional Karamea S-type granitic magmatism. Although estimated metamorphic conditions were insufficient for large amounts of melt to have been produced from Bonar Range pelites (calculated melt volumes are < 10%), they do provide evidence consistent with widespread heating and partial melting in the deeper crust.This heating episode was contemporaneous with partial melting in Fiordland (New Zealand) and West Antarctica, although Mesozoic thermal and deformational events complicate the Palaeozoic record in both those areas. Nevertheless, the apparent 1000 s km of along-strike crustal partial melting indicates that a continental-scale tectonic plate margin re-organisation took place at this time. The cause in the New Zealand segment was most likely, but not unequivocally, an extensional tectonic regime with an elevated geothermal gradient caused by conductive heating from a shallowed lithospheric mantle.